Protein Stores Regulate When Reproductive Displays Begin in the Male Caribbean Fruit Fly - Short, Clancy A.; Hatle, John D.; Hahn, Daniel A. (Frontiers in Physiology, 2020)
Many animals exhibit reproductive behavior that requires expenditure of valuable nutrients. In males of many species, competitive energetically demanding displays and the development of sexual ornaments require prior accumulation of nutrient stores. Males must coordinate nutrient stores with ornament development and reproductive displays or they risk depleting their resources mid-development or mid-display, reducing their chance of mating. Males may use nutrient stores to regulate their reproductive behavior. Amino acid reserves may be important for reproduction, but the roles of amino acid stores in initiating maturation and reproductive behavior are less studied than fat stores. Insects store amino acids as hexamerin storage proteins. Many fly species use a specific hexamerin, larval serum protein 2 (LSP-2), as both a juvenile storage medium and to store protein consumed after adult eclosion. Protein stored as LSP-2 has previously been suggested to regulate reproduction in females, but no role has been proposed for LSP-2 in regulating male maturation. We use males of the Caribbean fruit fly, Anastrepha suspensa, a species with nutrient-intensive male sexual displays to test whether LSP-2 stores regulate male reproductive displays. We fed adult A. suspensa males a diet with or without protein, then assayed these males for lsp-2 transcript abundance via qRT-PCR, LSP-2 protein abundance via Western blot, and reproductive display behavior via observation. We found that adult males with ad libitum dietary protein had greater lsp-2 transcript and protein abundance, earlier sexual display behavior, and were more likely to exhibit sexual display behavior than protein-deprived adult males. We show that lsp-2 knockdown via RNAi decreases the proportion of males exhibiting reproductive displays, particularly early in the onset of reproductive behavior. Our results suggest circulating LSP-2 protein stores regulate reproductive behavior in A. suspensa males, consistent with protein stores modulating reproduction in males with expensive reproductive strategies. Our results are consistent with hexamerin storage proteins performing dual roles of protein storage and protein signaling. Our work also has substantial practical applications because tephritid flies are a pest group and the timing and expression of male reproductive displays in this group are important for control efforts using the sterile insect technique.